2006
DOI: 10.1158/0008-5472.can-06-2240
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of PTEN Is Regulated by Ca2+ through a Tyrosil Phosphorylation–Independent Conformational Modification in Major Vault Protein

Abstract: We have recently shown in MCF-7 cells that nuclear phosphatase and tensin homologue deleted on chromosome 10 (PTEN) down-regulates phosphorylation of p44/42 and cyclin D1 and induces G 1 cell cycle arrest, whereas cytoplasmic PTEN down-regulates phosphorylation of Akt, up-regulates p27, and induces apoptosis. In this manner, nucleocytoplasmic partitioning of PTEN seems to differentially regulate the cell cycle and apoptosis. We have also reported that PTEN has nuclear localization signal-like sequences require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 25 publications
(41 reference statements)
1
62
0
Order By: Relevance
“…It has been reported that Ca 2 þ might be involved in tumorigenesis through multiple mechanisms including regulating Ras activity (Cook and Lockyer, 2006;Cullen and Lockyer, 2002), inducing PTEN nuclear translocation (Minaguchi et al, 2006) and modulating cell cycle. The increase in expression of Ca 2 þ channel proteins could enhance the Ca 2 þ influx and promote cell proliferation (Berridge et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Ca 2 þ might be involved in tumorigenesis through multiple mechanisms including regulating Ras activity (Cook and Lockyer, 2006;Cullen and Lockyer, 2002), inducing PTEN nuclear translocation (Minaguchi et al, 2006) and modulating cell cycle. The increase in expression of Ca 2 þ channel proteins could enhance the Ca 2 þ influx and promote cell proliferation (Berridge et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of nuclear PTEN are numerous but remain poorly studied compared with its cytoplasmic roles. PTEN translocates to the nucleus via multiple mechanisms, including monoubiquitination and interaction with major vault protein [56,57]. Its nuclear export appears dependent on active transport or association with Ran-guanosine triphosphatase [39,58].…”
Section: Pten Structure Localization and Signalingmentioning
confidence: 99%
“…This possibility was supported by the findings of Gil et al (14), who showed that nuclear import of PTEN is mediated through an NH 2 -terminal nuclear localization domain by a Ran GTPase-dependent pathway. Alternatively, it was suggested that the major vault protein could serve as a Ca 2+ -dependent surrogate shuttle protein that imports PTEN into the nucleus (17,18). Recent studies showed that PTEN could be ubiquitinated by NEDD4-1 (19).…”
Section: Introductionmentioning
confidence: 99%